Smartphone use and its association with academic performance among university students in Bangladesh - Md. Biplob Hossain; Noyon Ali; Ahmed Al Sabbir; Faysal Ahmed Imran; Md. Shahjahan (Institute of Advanced Engineering and Science, 2025)
Smartphone use has become integral to daily life, particularly among university students. While smartphones provide educational benefits, their overuse and addiction may negatively impact academic performance. This study investigates the prevalence of smartphone use, addiction levels, and their associations with academic performance among undergraduate students in Bangladesh. A cross-sectional survey was conducted on 615 undergraduate students from seven universities. The smartphone addiction scale-short version (SAS-SV) measured addiction levels, while academic performance was assessed via self-reported cumulative grade point average (CGPA). Descriptive statistics and logistic regression analyses were performed to explore associations. Among respondents, 29.1% were categorized as smartphone-addicted based on SAS-SV thresholds. Key predictors of higher academic performance (CGPA>3.0) included male gender (adjusted odds ratio (AOR): 3.71, 95% confidence interval (CI): 2.47–5.59, p<0.01), rural background (AOR: 1.64, 95% CI: 1.11–2.43, p=0.01), and attending private universities (AOR: 1.85, 95% CI: 1.28–2.74, p<0.01). Smartphone use for educational purposes was positively associated with better academic outcomes (AOR: 1.48, 95% CI: 0.95–2.30, p<0.01). Although smartphones are widely used for academic purposes, excessive use for stress relief or non-educational activities may harm academic outcomes. Interventions promoting responsible use and raising awareness about smartphone addiction are crucial for enhancing academic performance among university students.